The ecological security risks of bronopol: a focus on antibiotic resistance gene dissemination - Zhuocheng Yao; Yuhan Yang; Yanchun Gong; Shiyi Shi; Yunying Ge; Weiliang Zeng; Deyi Zhao; Jianming Cao; Jianming Cao; Tieli Zhou; Mo Shen (Frontiers in Microbiology, 2025)
Disinfectants are commonly utilized by humans to combat microorganisms. However, residual disinfectants may promote environmental antimicrobial resistance by facilitating horizontal gene transfer (HGT) of antibiotic resistance genes. Bronopol is a routinely used disinfectant that persists in the environment, and previous studies have concentrated on its ecotoxicity rather than its implications on the propagation of resistance genes. This study aimed to establish an in vitro conjugation model to investigate whether bronopol promotes the transfer of antibiotic resistance genes (ARGs) via plasmid conjugation. Using Escherichia coli DH5α and DC8855 as donors harboring RP4-7 and blaNDM-4-positive IncFII(K) plasmids, respectively, and J53 as the recipient strain, we found that sub-inhibitory concentrations of bronopol (2 μg/L and 20 μg/L) significantly increased the conjugative transfer frequency (CTF) of both plasmids. Mechanistic analysis revealed that bronopol enhanced bacterial membrane permeability, as demonstrated by propidium iodide (PI) staining, 1-N-phenylnaphthylamine (NPN) fluorescent probes, transmission electron microscopy (TEM), and upregulation of the outer membrane protein gene ompC. Additionally, bronopol treatment upregulated RP4 plasmid-encoded genes involved in DNA transfer/replication (trfAp) and the global regulator of HGT (kilA/kilB). These findings highlight a previously unrecognized role of bronopol in facilitating the dissemination of antibiotic resistance genes, particularly those of clinical significance.